2018
DOI: 10.1016/j.apmr.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Rehabilitation Interventions in Children Undergoing Hematopoietic Stem Cell Transplant With Thrombocytopenia

Abstract: Objective: To analyze the relationship between platelet counts, the intensities of physical therapies (PT) and occupational therapies (OT) services received, and the frequency of bleeding complications in children undergoing hematopoietic stem cell transplants (HSCT) during a period of severe thrombocytopenia. Design: Retrospective review study Setting: Tertiary care hospital Participants: Children (age <18) hospitalized for HSCT in 2010 and 2011 who received PT and OT services while markedly thrombocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
4
0
5
Order By: Relevance
“…Despite discrepancies in the quality of the trials, type of intervention, and methodology, none of the studies included in this review mentioned an adverse event as a direct result of rehabilitation exercise intervention. This finding is in line with other studies, where the children with severe thrombocytopenia undergoing HSCT were found to have only minor and relatively rare bleeding complications due to physical and occupational therapy interventions (Ibanez et al, 2018). Furthermore, the majority of the previous systematic reviews, despite eluding to the need for more robust clinical trials, have agreed that exercise is safe and has a positive impact on patients' physical function, HRQoL, and fatigue (Persoon et al, 2013;Van Haren et al, 2013;Kruijsen-Jaarsma et al, 2013;Oberoi et al, 2018…”
Section: No Adverse Effects Of Exercise Therapysupporting
confidence: 93%
“…Despite discrepancies in the quality of the trials, type of intervention, and methodology, none of the studies included in this review mentioned an adverse event as a direct result of rehabilitation exercise intervention. This finding is in line with other studies, where the children with severe thrombocytopenia undergoing HSCT were found to have only minor and relatively rare bleeding complications due to physical and occupational therapy interventions (Ibanez et al, 2018). Furthermore, the majority of the previous systematic reviews, despite eluding to the need for more robust clinical trials, have agreed that exercise is safe and has a positive impact on patients' physical function, HRQoL, and fatigue (Persoon et al, 2013;Van Haren et al, 2013;Kruijsen-Jaarsma et al, 2013;Oberoi et al, 2018…”
Section: No Adverse Effects Of Exercise Therapysupporting
confidence: 93%
“…Studies in patients with acute brain injury, dementia, and serious mental illness support the efficacy and feasibility of exercise despite cognitive issues. [49][50][51] Although thrombocytopenia is not considered a contraindication to exercise, in keeping with data in stem cell transplant patients, 52 exercises with high risk of injury or falling should be avoided, especially if platelets are <20,000/ll.…”
Section: Cirrhosis-related Safety Considerationsmentioning
confidence: 87%
“…Normally, a platelet count less than 20,000/mL would be considered as a relative contraindication for exercises, whereas patients with platelet counts between 20,000 and 30,000/mL could perform gentle nonresistance exercises, 30,000 to 50,000/mL minimal resistance (1 to 2 pound) exercises, 50,000 to 150,000/mL progressive resisted exercises, and 150,000/mL and beyond no restrictions [51]. There is, however, growing evidence that even with critically low platelets (10,000 to 50,000 /mL), patients can perform carefully designed exercises without any additional risk factors, if they are monitored and supervised by an experienced therapist [52,53].…”
Section: Pt and The Safety Of Physical Activity After Hsctmentioning
confidence: 99%